Isotypic profiles of antibody responses to Toxoplasma gondii infection in rats and mice: kinetic study and characterization of target antigens of immunoglobulin A antibodies. - Godard, I (1990)
The antibody responses to Toxoplasma gondii were investigated in rat and mouse experimental models. The immunoglobulin A (IgA) antibody response was of particular interest because acquisition of Toxoplasma gondii is usually by the oral route. The rat model was used because the natural resistance of rats to the parasite is similar to the natural resistance exhibited by adult humans. There was an early and simultaneous rise in IgA and IgM antibody responses. The IgA antibody response was maximal around day 40. IgA antibodies from Fischer rats were mainly directed against soluble and membrane antigens of 28.5, 29, 30, 35, and 38 kilodaltons (kDa). In mice, however, a major antigen of 29 kDa was recognized by IgA antibodies. Moreover, in orally infected rats, an intense IgE antibody response against the major surface antigen, P30, was observed. An IgA antibody response was also observed in rats and mice immunized with Toxoplasma excreted-secreted antigens, even without adjuvant. This response was mainly directed against 28.5- and 34-kDa antigens in rats. Serum IgA from infected rats tested against the excreted-secreted antigens bound to 28.5- 34-, and 39-kDa antigens, whereas sera from infected mice recognized only the 34-kDa antigen.